Prevalence of insomnia and its association with quality of life among Macau residents shortly after the summer 2022 COVID-19 outbreak: A network analysis perspective - Chen, Pan; Zhang, Ling; Sha, Sha; Lam, Mei Ieng; Lok, Ka-In; Chow, Ines Hang Iao; Si, Tong Leong; Su, Zhaohui; Cheung, Teris; Feng, Yuan; Jackson, Todd; Xiang, Yu-Tao (Frontiers in Psychiatry, 2023)
Background: The latest wave of the coronavirus disease 2019 (COVID-19) pandemic in Macau began on June 18, 2022 and was more serious than previous waves. Ensuing disruption from the wave is likely to have had a variety of negative mental health consequences for Macau residents including increased risk for insomnia. This study investigated the prevalence and correlates of insomnia among Macau residents during this wave as well as its association with quality of life (QoL) from a network analysis perspective. Methods: A cross-sectional study was conducted between July 26 and September 9, 2022. Univariate and multivariate analyses explored correlates of insomnia. Analysis of covariance (ANCOVA) examined the relationship between insomnia and QoL. Network analysis assessed the structure of insomnia including “Expected influence” to identify central symptoms in the network, and the flow function to identify specific symptoms that were directly associated with QoL. Network stability was examined using a case-dropping bootstrap procedure. Results: A total of 1,008 Macau residents were included in this study. The overall prevalence of insomnia was 49.0% (n=494; 95% CI=45.9-52.1%). A binary logistic regression analysis indicated people with insomnia were more likely to report depression (OR=1.237; P<0.001) and anxiety symptoms (OR=1.119; P<0.001), as well as being quarantined during the COVID-19 pandemic (OR=1.172; P=0.034). An ANCOVA found people with insomnia had lower QoL (F (1, 1,008)=17.45, P<0.001). “Sleep maintenance” (ISI2), “Distress caused by the sleep difficulties” (ISI7) and “Interference with daytime functioning” (ISI5) were the most central symptoms in the insomnia network model, while “Sleep dissatisfaction” (ISI4), “Interference with daytime functioning” (ISI5) and “Distress caused by the sleep difficulties” (ISI7) had the strongest negative association with QoL. Conclusion: The high prevalence of insomnia among Macau residents during the COVID-19 pandemic warrants attention. Being quarantined during the pandemic and having psychiatric disorders were the risk factors for insomnia. Future effective interventions can prioritize the central symptoms and symptoms linked to QoL observed in our network models to improve insomnia and QoL.